Bridging Gender Differences : Exploring the Effect of Social Support and Campus Culture on Self-Regulated Learning in Higher Education - Fawziah Zahrawati B; Jumaisa Jumaisa; Andi Aras (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to examine self-regulated learning based on gender using two factors, namely social support and campus culture, and analyze the moderation effects presented by these two factors. This study was a quantitative approach with an expost facto method. The population was all students in the Social Sciences Education Study Program of the Parepare State Islamic Institute for the 2019-2023 batch of 116 students. There were 34 men and 82 women. The research sample took a saturated sample, namely the entire population. The data collection techniques were questionnaires, documentation, and interviews. Testing the research hypothesis was carried out using SmartPLS. The study found that social support significantly increased SRL, with a stronger effect on male students than female students. A positive campus culture also increases SRL, but its effect is weaker on female students. Campus culture moderates the effect of social support on SRL, amplifying its effectiveness, especially in male students. Social support also moderated the effect of campus culture on SRL, strengthening the motivation and confidence of male students, although the impact was slightly weaker on female students but still relevant. These results suggest that social support and campus culture enhance SRL, particularly among male students. It is crucial to design interventions that consider gender differences to achieve the best possible results.